Clinical Outcomes of Autologous Osteochondral Transplantation for Osteochondral Lesions of the Talus: An Age-Based Multivariable Analysis. Issue 4 (November 2022) - Azam, Mohammad T.; Weiss, Matthew B.; Colasanti, Christopher; Brodeur, Peter G.; Ubillus, Hugo A.; Kennedy, John G.
Category: Sports; Ankle; Hindfoot; Other Introduction/Purpose: Osteochondral lesions of the talus (OLT) are common injuries that are often found in patients with chronic disabling pain after ankle sprains. While OLT is becoming increasingly prevalent in the younger active population, there is disagreement and a lack of strong evidence about the impact of age on outcomes. The purpose of this study is to perform an Age- Based multivariate analysis to evaluate the clinical outcomes of Autologous Osteochondral Transplantation (AOT) for the treatment of OLT. The goals of this study are to examine trends in patient characteristics and clinical outcomes that occur with age as a statistical variable when performing AOT for the treatment of OLT. Methods: All study protocols were approved by the Institutional Review Board at the senior author's institution. A retrospective cohort study using chart review for AOT procedures on approximately 80 patients from 2006 to 2019 performed by a single surgeon. Clinical outcomes of patients were evaluated via FAOS scores for Symptoms, Pain, Activities of Daily Living, Sports and Quality of Life. A multivariable linear regression was used to assess the independent factors predictive of the first post-operative FAOS after AOT. The independent variables included in the model were pre-operative FAOS, age, defect size, whether the lesion was a shoulder lesion, cystic lesion, or a result of a traumatic injury, and whether the patient had a prior microfracture surgery. A p-value <.05 was considered significant and 95% confidence limits (95% CL) for regression coefficient estimates (est.) were calculated. Results: 78 patients were included in the analysis with an average age of 35.5 +- 13.6. The average follow-up was 54.4 months +- 18.9 months, average pre-operative FAOS was 54.3 +- 19.4 and the average post-operative FAOS was 83.4 +- 13.6. The average defect size was 109.3 mm 2 (std. dev. = 62.4 mm). 56 patients had a shoulder lesion, 24 had a prior microfracture surgery, 42 had a cystic lesion, and 27 had a prior traumatic injury. The multivariable linear regression showed that the pre-operative FAOS was associated with a higher post-operative FAOS (est., 95% CL: 0.16, 0.012 - 0.307; p=0.034). Defect size (est., 95% CL: -0.05, -0.097 - -0.003; p=0.0358), having a shoulder lesion (est., 95% CL: -9.068, -15.448 - -2.688; p=0.006), or having a prior microfracture surgery (est., 95% CL: -7.07, -13.118 - -1.021; p=0.0226) were associated with a lower post-operative FAOS. Conclusion: The main finding of this study is patient age was not an independent risk factor for inferior clinical outcomes after AOT for OLT. Additionally, having a cystic lesion, or having a lesion because of a traumatic injury were not significantly associated with post-operative FAOS. Having a shoulder lesion had the largest marginal effect on post-operative FAOS. These findings provide important information for providers when counseling and selecting patients for AOT procedure for treatment of OLT.